Current approaches to the development of beach sports - Стенли Маккензи; Татьяна Кропивницкая; Ольга Девятаева (National University of Physical Education and Sport of Ukraine, 2016)
The paper is devoted to the analysis of the preconditions for origination and peculiarities of the formation of beach team sports (volleyball, handball, football) in the world, along with the generalization of international experience of their functioning at the present stage of the development of sport. In the paper, the balance of forces in the international sports arena is examined and Brazilian national teams were found to occupy leading positions in this group of sports. Conditions ensuring effective functioning of beach team sports in this country are analyzed. The prospects for their further development are identified.